Effect of Phytophthora infestans in the physiology and induction of pathogen related proteins in Physalys peruviana (2010)
Phytophthora infestansis a plant pathogen that affects a great variety of crops within the Solanaceae family. In 2007 the pathogen was described causing disease in Physalis peruviana (cape gooseberry). Since the report of the disease, we have studied this particular interaction. The aim of this work was to characterize the first defense reactions produced on cape gooseberry leaves due to the infection with P. infestans. Detached cape gooseberry leaves were inoculated with a solution of 103sporangia/ml. Electron microscopy photographs were taken at 0, 24, 48, 72 and 96 hours post inoculation on the leaf, abaxial surface up. Reactive oxygen species (ROS), and the induction of Pathogenesis Related (PR) proteins were measured after inoculation. We also performeda qRT-PCR in order to investigate the molecular bases of this interaction. We have evidenced sporangial germination and active aerial growing of Phytophthora on the leaf surface. There is an induction in the expression of carbonic anhydrase and glucanase Agenes, as well as other markers related to the plant defense response. In particular, we detected the induction of the enzymes peroxidase and glucanase as well as the production of ROS. To our knowledge, this is the first study that characterizes the first biochemical reactions caused by P. infestans on cape gooseberry. Our results are fundamental for understanding how P. infestans affects other members of the Solanaceae family.